Open Seminar on Acoustics OSA'2007 - Rdzanek, Witold; Leniowska, Lucyna (Archives of Acoustics, 2007)
It is our pleasure to present the papers submitted for the 54th Open Seminar on Acoustics – OSA 2007 – that was held September 10–14, 2007 in the city of Przemyśl located in the South-East Poland. The conference was organized jointly by the Rzeszów Division of the Polish Acoustical Society, by the Committee of Acoustics at the Polish Academy of Sciences, and also by the Institute of Physics and the Institute of Technology – both part of the Faculty of Mathematics and Natural Sciences at the University of Rzeszów in Poland.The conference was attended by 120 scientists. There were 5 plenary and 91 contributed lectures. We continued with the tradition of poster presentation session to facilitate the maximum participation.This volume represents the diversity of contributions to the conference. We distinguished 13 different aspects of theoretical and experimental research in the field of acoustics. The papers were organized in the alphabetic order according to the topics:• General Linear Acoustics,• Nonlinear Acoustics,• Ultrasonics, Quantum Acoustics and Physical Effect of Sound,• Biomedical Acoustics,• Acoustooptics,• Speech Acoustics,• Musical Acoustics,• Room Acoustics,• Structural Acoustics,• Noise, its Effects and Control,• Electroacoustics,• Hydroacoustics,• Psychoacoustics.The Journal Archives of Acoustics used a regular peer review system in the selection of the submitted papers. Every paper was reviewed by two independent reviewers acquainted with the subject.We wish to express our special thanks to the reviewers for their active interest in the publishing progress of this volume. We also should like to thank the authors for preparing their manuscripts and also for correcting them fast so that most of them could be accepted for publication a month after the conference. We hope that this volume will meet the needs of the readers of the Journal.